Plagiarism among FPPSM undergraduates' final year project : trace study from year 1994 to 2009 [electronic resource] - Nor Azwani Jusoh, 1988- (2011)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2011